2001
DOI: 10.1021/bi0024411
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the FAD-Containing N-Methyltryptophan Oxidase from Escherichia coli

Abstract: N-Methyltryptophan oxidase (MTOX) is a flavoenzyme that catalyzes the oxidative demethylation of N-methyl-L-tryptophan and other N-methyl amino acids, including sarcosine, which is a poor substrate. The Escherichia coli gene encoding MTOX (solA) was isolated on the basis of its sequence homology with monomeric sarcosine oxidase, a sarcosine-inducible enzyme found in many bacteria. These studies show that MTOX is expressed as a constitutive enzyme in a wild-type E. coli K-12 strain, providing the first evidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 36 publications
1
57
0
Order By: Relevance
“…Direct intracellular enzymatic formaldehyde release can be induced in E. coli by providing N-MeTrp in the growth medium. This serves as substrate for MTOX, a constitutively expressed E. coli enzyme homologous to the N-terminal amine oxidase domain of DMGO (41,42). Unlike DMGO, MTOX does not contain (or is not associated with) 5,10-CH 2 -THF synthase activity, and oxygen-dependent N-MeTrp oxidation results in the formation of Trp and formaldehyde.…”
Section: An In Vivo Reporter System For Intracellular Formaldehyde-mentioning
confidence: 99%
See 1 more Smart Citation
“…Direct intracellular enzymatic formaldehyde release can be induced in E. coli by providing N-MeTrp in the growth medium. This serves as substrate for MTOX, a constitutively expressed E. coli enzyme homologous to the N-terminal amine oxidase domain of DMGO (41,42). Unlike DMGO, MTOX does not contain (or is not associated with) 5,10-CH 2 -THF synthase activity, and oxygen-dependent N-MeTrp oxidation results in the formation of Trp and formaldehyde.…”
Section: An In Vivo Reporter System For Intracellular Formaldehyde-mentioning
confidence: 99%
“…3B). The expression of MTOX is enhanced by the presence of N-MeTrp (42), and the fluorescence values we obtained were therefore normalized versus total MTOX enzyme activity in the corresponding cellular extracts. We demonstrated that a response to intracellular formaldehyde formation is obtained from levels as low as 0.1 M N-MeTrp with a nonlinear increase in the fluorescence per unit of enzyme activity obtained within the range of N-MeTrp tested.…”
Section: An In Vivo Reporter System For Intracellular Formaldehyde-mentioning
confidence: 99%
“…Use of Sarcosine As Sole Nitrogen Source by E. coli Expressing AtSOX-Wild type E. coli uses glycine as the sole nitrogen source (34) but is not expected to use sarcosine as efficiently because of low endogenous SOX activity (35). Consistent with this prediction, growth of wild type cells on plates was poor when sarcosine replaced glycine as the nitrogen source ( Fig.…”
Section: Searches Of Genbankmentioning
confidence: 72%
“…Import Reactions-In vitro protein import reactions (final volume 200 l) were initiated by adding 35 S-labeled glycolate oxidase or AtSOX (5 ϫ 10 5 cpm trichloroacetic acid-precipitable protein) to 350 g of glyoxysomes in the presence of import buffer (25 mM Mes-KOH, pH 6.0, 0.5 M sucrose, 10 mM KCl, 1 mM MgCl 2 , and 5 mM MgATP). The reaction temperature was 26°C unless otherwise noted.…”
Section: Chemicals and Reagents-[n-methyl-mentioning
confidence: 99%
“…This family is mainly composed of considerably smaller, monomeric proteins (~44 kDa) that contain covalently bound FAD as the only prosthetic group and exhibit modest sequence homology (~20% identity) with the β subunit of TSOX. Members of this family include monomeric sarcosine oxidase (MSOX), N-methyltryptophan oxidase (MTOX), pipecolate oxidase and nikD [11][12][13][14][15][16][17][18] . Crystal structures have been determined for MSOX 11, 14 , a monofunctional enzyme that exhibits sarcosine oxidase but not 5,10-CH 2 -H 4 folate synthase activity 5 .…”
Section: Introductionmentioning
confidence: 99%